2008
DOI: 10.1002/dc.20822
|View full text |Cite
|
Sign up to set email alerts
|

Are adjunctive markers useful in routine cervical cancer screening? Application of p16INK4a and HPV‐PCR on ThinPrep samples with histological follow‐up

Abstract: The objectives of the study were to evaluate 1) the diagnostic sensitivity and specificity of p16(INK4a) as a marker for high-grade cervical lesions, 2) the results of a real-time polymerase chain reaction detecting high-risk human papillomavirus, and 3) the interobserver variability of the p16(INK4a) interpretation.A total of 232 ThinPrep samples were stained for p16(INK4a), and HPV-DNA PCR was performed on 107 specimens with inclusion of both benign and abnormal cytology. Histological follow-up information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
2
15
0
1
Order By: Relevance
“…Twelve studies 2325;2833;3638 used clone E6H4 as a primary antibody for p16 INK4a , other primary antibodies used were Clone 6H12 27 , Clone JC8 34 and 16P04 35 . Positivity criteria of p16 INK4a immunostaining differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies 2325;2833;3638 used clone E6H4 as a primary antibody for p16 INK4a , other primary antibodies used were Clone 6H12 27 , Clone JC8 34 and 16P04 35 . Positivity criteria of p16 INK4a immunostaining differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was a difference in the localization of the immunostaining. Two studies 27;36 only considered nuclear staining as a positive p16 INK4a staining reaction while 8 studies 23;24;28;29;31;32;34;35 considered both nuclear and/or cytoplasmic staining as a positive reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In cervical cytology, various research studies have been performed to evaluate the potential usefulness of applying p16 immunocytochemical staining protocols, especially for the triage of equivocal or mildly abnormal Pap cytologic results. In most studies, a sensitivity similar to that of HPV testing, but at a substantially higher specificity rate, has been reported for p16 cytology when used for the triage of Pap cytologic results categorized as ASC-US or LSIL or containing atypical glandular cells [9][10][11][12][13][14] (reviewed by Cuschieri and Wentzensen 6 and Tsoumpou et al 8 ). Although this indicates the potential of p16 cytologic testing for the triage of abnormal Pap cytologic results, many of the research studies show limitations owing to the use of nonvalidated and nonstandardized immunocytochemical reagents and protocols, the lack of standardized interpretation protocols, and a low number of biopsy follow-up results available.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the majority of the studies, p16 cytology was found to provide sensitivity rates for the detection of underlying high-grade cervical intraepithelial neoplasia (CIN of grade 2 or higher, CIN2þ), which were similar or slightly lower compared with the sensitivity of testing for the presence of human papillomavirus (HPV) infections. 7,9,10,11 At the same time, specificity of p16 cytology-based testing was found to be substantially higher than the specificity of HPV testing in all studies.…”
mentioning
confidence: 99%